Synthesis, assembly and applications of novel two-dimensional metal chalcogenide nanomaterials - Tan, Chaoliang (2016)
The ability to prepare novel two-dimensional (2D) metal chalcogenide nanosheets and heteronanostructures or construct novel nanostructures via self-assembly by using 2D metal chalcogenides as basic building blocks is of great importance for the further exploration of their properties and varying potential applications. In the light of this, my aim in this thesis is to synthesize novel 2D metal chalcogenide nanosheets and heteronanostructures or assemble 2D metal chalcogenide nanosheets into new nanostructures and then explore their potential applications in fluorescent biosensors, dye-sensitized solar cells, Li-ion batteries and digital data storage devices. First, I prepared two solution-dispersed ultrathin 2D ternary metal chalcogenide nanosheets, i.e. Ta2NiS5 and Ta2NiSe5, in high-yield and large scale in liquid phase by exfoliating their layered bulk crystals via the electrochemical Li-intercalation and exfoliation method. The sizes of the Ta2NiS5 and Ta2NiS5 nanosheets are 0.05-2 μm. Significantly, the yield for the single-layer Ta2NiS5 nanosheet reached up to ca. 86%. The single-layer Ta2NiS5 nanosheet was used as a novel sensing platform to construct fluorescent biosensor for DNA detection. Second, I achieved the high-yield and scalable production of single-layer alloyed MoS2xSe2(1-x) and MoxW1-xS2 nanosheets with high concentration (~66%) of metallic 1T phase by exfoliation of their micro-sized 2H-phase layered bulk crystals using the electrochemical Li-intercalation and exfoliation method. The MoS2xSe2(1-x) nanosheet thin film casted on a fluorine-doped tin oxide (FTO) substrate by the drop-casting method was directly used as an efficient electrocatalyst for the tri-iodide reduction at counter electrode in a dye-sensitized solar cell without any post-treatments. A power conversion efficiency of 6.5% was achieved on the MoS2xSe2(1-x) nanosheet thin film electrode, which is higher than that of 2H-phase MoS2xSe2(1-x) (5.4%). Third, I prepared three kinds of 2D metal chalcogenide heteronanostructures in liquid phase by an electrochemical method by using metal foils and bulk TiS2 crystal as precursors, in which metal sulphide nanoplates, including CuS, ZnS and Ni3S2, were epitaxially grown on ultrathin TiS2 nanosheet. TEM analyses revealed that these metal sulphide nanoplates were aligned on the TiS2 with perfect epitaxial alignment effect to vertical 2D epitaxial heteronanostructures. Moreover, when used as the anode in a Li ion battery, the CuS-TiS2 heteronanostructure-based electrode exhibited good performance. Last, I developed a facile and universal approach for the high-yield and scalable preparation of chiral nanofibers by the self-assembly of various ultrathin 2D nanomaterials, including single-layer graphene oxide (GO), MoS2, TaS2, TiS2, few-layer TaSe2, WSe2 and Pt nanoparticle-decorated reduced graphene oxide (Pt-rGO) or MoS2 (Pt-MoS2), in vigorously stirred polymeric solutions. These chiral nanofibers can be further transformed into same-handed helical nanorings with a diameter of 400-800 nm via a second assembly process. Chiral MoS2 nanofiber with P123 was integrated into a resistive memory device as the active layer. Impressively, the fabricated memory device presented a non-volatile flash memory behavior with excellent reproducibility and good stability.